From hierarchies to networks: The organizational evolution of the international drug trade. (December 2020) - McCarthy-Jones, Anthea; Doyle, Caroline; Turner, Mark
Abstract: The evolution of the transnational drug trade has precipitated an organizational and operational restructuring of organized crime groups (OCGs). This restructuring has produced a move away from formerly hierarchical and tightly controlled organizations, to more loosely coupled and decentralized network forms. But what has motivated the OCGs to restructure into more loosely coupled networks? Through an examination of the activities and strategies of Latin American OCGs, this article identifies market considerations, network responses to law enforcement pressure, and centrifugal forces within OCG networks as the key drivers of these changes. Despite this, OCGs still require some sort of organizational glue that connects and facilitates the activities of these decentralized networks. This is precisely why brokers are becoming vital actors in criminal networks. The data presented in this article suggests that brokers have assumed great significance in networks especially in relation to the ongoing linkages occurring between Latin American OCGs and with those in the Asia-Pacific.